2020
DOI: 10.5489/cuaj.6975
|View full text |Cite
|
Sign up to set email alerts
|

Canadian Urological Association guideline for the management of bladder and bowel dysfunction in children

Abstract: Afshar et al Guideline: Pediatric bladder and bowel dysfunction 2 © 2020 Canadian Urological Association classify the type, and evaluate the severity of this complex clinical diagnosis. These instruments have also been used to follow clinical response to treatment (8,9,10).The treatment of bowel dysfunction is an essential part of the overall management and should not be overlooked. The scope of the current guidelines is limited to the management of the lower urinary tract.The purpose of these guidelines is to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Several validated voiding scales are useful for this purpose ( 3 , 5 ), including the Dysfunctional Voiding Symptom Score (DVSS) ( 8 ) and the Vancouver Symptom Score (VSS) ( 9 ). Scored questionnaires help diagnosis, allow measurement of severity, and monitor the effectiveness of treatment ( 3 , 5 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several validated voiding scales are useful for this purpose ( 3 , 5 ), including the Dysfunctional Voiding Symptom Score (DVSS) ( 8 ) and the Vancouver Symptom Score (VSS) ( 9 ). Scored questionnaires help diagnosis, allow measurement of severity, and monitor the effectiveness of treatment ( 3 , 5 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Standard urotherapy and constipation management are the mainstay of treatment for BBD, and should be given as first-line therapy [ 13 , 17 ]. Pharmacotherapy of LUTD and surgical treatment should be considered only in patients who fully complied with, but failed first-line treatment after 6 months [ 2 , 18 ]. In our study, we found that BBD children treated with standard urotherapy and constipation management had significant improvement in DVSS as early as 3 months, and further improvement at 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, BC therapy is based on international guidelines, including those of the society of urologic oncology (SUO) [36], the National Comprehensive Cancer Network (NCCN) [37], the Canadian Urological Association (CUA) [38], the National Cancer Institute (NCI) [39], the First International Consultation on Bladder Tumors (FICBT), Consultation on Bladder Cancer (SIU-ICUD) [40], the PDQ bladder cancer [41], the American Urological Association (AUA) [42], the European Society for Medical Oncology (ESMO) [43] and the European Association of Urology (EAU) [44]. This practice has the drawback of not necessarily, accurately or appropriately recommending the options and alternatives as mentioned in the local recommendations for local clinical practice or specific cancer states.…”
Section: Redjdal Et Al Reported That the Guideline-based Dss (Gl-dss)...mentioning
confidence: 99%